Aktualisasi Etika Profesi Pustakawan Menuju Kualitas Layanan Prima - Ma'rifah, Siti (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
The role of professional librarians who apply good ethics in fulfilling their duties and profession is very important in managing to achieve excellent service. Professional librarians must maintain their professionalism in maintaining standards and quality of service quality for the benefit of the profession, professional organizations and service users. This article describes the actualization of librarian professional ethics towards excellent service quality with research using literature review methods. The results of the discussion show that to support ethical services, the application of the Librarian Code of Ethics is very important, where the code of ethics is a guideline for librarians in carrying out their duties optimally, optimally and professionally towards improving the quality of excellent service. The role of a professional librarian always has good ethics reflected in an attitude of responsibility, caring, responsiveness, courtesy and wisdom, as well as good communication skills.